Teaching Literature to adolescents. - Beach, Richard; Appleman, Deborah; Fecho, Bob; Simon. Rob (Routledge Taylor & Francis Group, 2021)
Now in its fourth edition, this popular textbook introduces prospective and practicing English teachers to current methods of teaching literature in middle and high school classrooms. This new edition broadens its focus to cover important topics such as critical race theory; perspectives on teaching fiction, nonfiction, and drama; the integration of digital literacy; and teacher research for ongoing learning and professional development. It underscores the value of providing students with a range of different critical approaches and tools for interpreting texts. It also addresses the need to organize literature instruction around topics and issues of interest to today’s adolescents. By using authentic dilemmas and contemporary issues, the authors encourage preservice English teachers and their instructors to raise and explore inquiry-based questions that center on the teaching of a variety of literary texts, both classic and contemporary, traditional and digital.